Soil Organic Carbon and Nitrogen Storage and Distribution in the Agricultural Soils as Affected by Soil Depths and Inundation Land Types: Soil Organic Carbon and Nitrogen Storage - Uddin, M J; Mohiuddin, A S M (Journal of the Asiatic Society of Bangladesh, Science, 2025)
A study was initiated on soil organic carbon (SOC) and total nitrogen (TN) storage and their distribution as affected by soil depths and inundation land types selecting ideal two catena across eight soil profiles up to the depth of 120 cm in the Brahmaputra and the Ganges alluviums. Soil organic carbon and TN storage is higher in the surface soil depth than the other soil depths. The contents and distribution of SOC and TN in all the soil depths varies significantly. Moreover, inundation land types and soil depths exhibited a significant effect (p<0.001) on SOC and TN storage. Soil organic carbon and TN storage were higher in the lowland (LL) and medium lowland (MLL) sites than that in the highland (HL) and medium highland (MHL) sites across the alluviums, which indicates that the topographic variability as well as their water recession conditions which ultimately focuses on SOC loss or sequestration. The Brahmaputra alluvium possesses higher SOC and TN storage than the Ganges alluvium which may be due to the variability of their land use and local management practices. Proper emphasis should be given on sub soil depths and inundation levels in formulating any agricultural policy planning. J. Asiat. Soc. Bangladesh, Sci. 50(1-2): 137-152, June-December 2024